2001
DOI: 10.1248/jhs.47.136
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of the Effects of 2,3,7,8-Tetrachlorodibenzo-p-dioxin on Murine Testicular Leydig and Sertoli Cells.

Abstract: We treated testicular cell lines Leydig TM3 and Sertoli TM4 with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and used two-dimensional electrophoresis to investigate the resulting protein alterations. Cells were cultured in a medium containing 10 -5 to 10 nM TCDD for 4 hr, under which condition viability was not affected. Protein expression was compared semi-quantitatively by silver staining, by autoradiography of [35 S] methionine-labeled proteins, and by anti-phosphotyrosine antibody. In TM3, 34 protein spots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…It thus remains to be investigated if changes in these CYP enzymes are detectable 3 wk postadministration. It is worthwhile to note that in these 2-DE studies on the effects of TCDD in different tissues, no alterations in CYP were mentioned [29,41]. Besides the binding to the AhR, other mechanisms such as oxidative stress and other types of cellular stress mechanisms have been proposed to play an important role in TCDD induced toxicity [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thus remains to be investigated if changes in these CYP enzymes are detectable 3 wk postadministration. It is worthwhile to note that in these 2-DE studies on the effects of TCDD in different tissues, no alterations in CYP were mentioned [29,41]. Besides the binding to the AhR, other mechanisms such as oxidative stress and other types of cellular stress mechanisms have been proposed to play an important role in TCDD induced toxicity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Solvent A: 0.1% FA in HPLCgrade water; solvent B: 0.1% FA in ACN. The column outlet was coupled to the Q-Tof through a stainless steel capillary (Proxeon, Odense, Denmark) at 1.9 kV, with the cone voltage at 30 V. The eluting [M 1 2H] 21 , [M 1 3H] 31 , and [M 1 4H] 41 peptides (in the 400-1200 m/z range) were automatically selected and fragmented using predefined collision energy profiles. For direct infusion MS and MS/MS analysis, the peptide sample was ZipTip-concentrated and loaded into a Au/Pd-coated nanospray needle (Proxeon) and a capillary voltage of 800 V was applied.…”
Section: Silver Staining and Mass Spectrometric Protein Identificationmentioning
confidence: 99%
“…49) Further, the two-dimensional gel electrophoresis system has been improved and adapted to TOF/MS system for analyzing proteome. 68) Finding of specific AhR ligand(s) 84) and inhibitors 85,86) could also help the interpretation of data. Taken together, it is likely that biochemical approaches which are based on the endpoint of the toxicity caused by dioxins are also important in understanding the pleiotropic effects.…”
Section: Cyp1a1mentioning
confidence: 99%
“…We previously carried out proteomic 12) and RNA arbitrarily primed polymerase chain reaction analyses 11) of mouse Leydig TM3 cells exposed to TCDD and reported that the synthesis of proteins and expression of mRNAs were markedly altered by TCDD. Taking those findings together with the present results, we believe that TCDD may have an effect on testis function but that it may not affect testosterone production directly.…”
Section: Dose-and Time-dependent Effects Of Tcdd On Testosterone Secrmentioning
confidence: 99%
“…Mediation of the toxic effects of TCDD via aryl hydrocarbon receptors (AhR) and AhR nuclear translocators, in particular, have been clarified. 10) To investigate the effects of TCDD on the testis at the mRNA or protein level, experiments using testicular cells derived from the mouse have been carried out, and many interesting genes 11) and proteins 12) have been found. We investigated the direct effects of TCDD on the secretion of testosterone from mouse testicular cells and examined the viability of cells and concentrations of testosterone when primary cultured mouse testicular cells were exposed to TCDD.…”
Section: Introductionmentioning
confidence: 99%